PERANCANGAN DASHBOARD PENGAWASAN AKTIVITAS TRUK PADA PT CIPTA NIAGA SEMESTA - Raharja , David (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
PT. Mayora Indah Tbk. (Mayora) was founded in 1977 with the first factory located in Tangerang with the target market in Jakarta and its surroundings. Currently, Mayora needs a way to monitor the activities of distribution trucks or truck vendors, such as data on incoming and outgoing factory trucks, data on goods transported by trucks, and unloading goods from trucks to assess employee key performance indicators. Therefore the author proposes to design a dashboard for monitoring truck activity at PT Cipta Niaga Semesta using Pentaho and Grafana with the prototyping method and the nine-step Kimball method. Pentaho is a business intelligence software, while Grafana is a multiplatform open source analytics and interactive visualization web application. The feature that will be made is a dashboard that displays truck activity data with filter options to display the data you want to see.